2009
DOI: 10.1007/s00530-009-0171-3
|View full text |Cite
|
Sign up to set email alerts
|

Ubimedia based on readable and writable memory tags

Abstract: Ubimedia is a concept where media files are embedded in everyday objects and the environment. We propose an approach where the user can read and write these files with his/her personal mobile phone simply by touching the physical objects. This facilitates easy access and storage of, e.g. video and audio files related to the physical object in question. This paper describes our work in developing a technical solution for ubimedia and studying user acceptance of forthcoming ubimedia services. Our technical devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The information presented by the prototypes determines the category of the cognitive domain [ 20 ]that receives the learning support. For example, the prototype in [ 29 ] presents support on remembering factual knowledge. For this prototype NFC tags have been attached to everyday objects.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The information presented by the prototypes determines the category of the cognitive domain [ 20 ]that receives the learning support. For example, the prototype in [ 29 ] presents support on remembering factual knowledge. For this prototype NFC tags have been attached to everyday objects.…”
Section: Resultsmentioning
confidence: 99%
“… GPS Knowledge of criteria and standards Heart rate monitors Jraidi, I., & Frasson, C. (2012) [ 38 ] Cognitive - EEG It detects the uncertainty of students while performing exercises in an intelligent tutoring system. Kaasinen et al ., (2009) [ 29 ] Cognitive - NFC It reads tags placed in objects in order to present more information Kanjo(2009) [ 42 ] MobAsthma Cognitive - Air pollutants sensors It measures the air pollution and compares it asthma cases. GPS Software sensors Kanjo(2009) [ 42 ] NoiseSpy Cognitive - GPS It measures the noise pollution.…”
Section: Identified Sensors Together With Their Measured Property Andmentioning
confidence: 99%
“…Experimental intelligent environments have been built in enclosed spaces such as laboratories, homes and museums, where the technical arrangements are manageable and affordable, and where there are fewer stakeholders involved. Research results on intelligent environments have been described in the fields of housing [16][17][18], health [18,19], assisted living [20][21][22][23], ambient media [13,24] as well as security and safety [18,23,25,26]. These application fields are often interconnected as, for instance, home services may include security features.…”
Section: Characteristics Of Intelligent Environmentsmentioning
confidence: 99%
“…The results by Kaasinen et al [84] indicated that the best technique for touching would probably be having a 'touch mode' that can be activated and deactivated either manually or automatically. More recently, Kaasinen et al [24] have studied the acceptance and user experience of touchable memory tags. Ease of upload and fun interaction were identified as the main strengths of such an interaction metaphor.…”
Section: User Experience and Expectations Of Haptic Tangible And Tacmentioning
confidence: 99%
See 1 more Smart Citation